Alternative forced-molting methods in japanese quails - SILVA,Daiane Batista (2017)
SUMMARY The aim of this study was to evaluate the effects of different forced-molting methods on the performance and quality of laying quail eggs. The experiment was conducted in a conventional shed for quails and lasted 115 days. 480 Japanese quails at an initial age of 52 weeks were used. The following treatments were evaluated: total feed fasting (control treatment); corn and soybean bran diet; high- zinc diet (7,300 ppm); wheat bran diet; and ground corn diet. A fully randomized experimental outline was used with 5 treatments and 4 repetitions. Each lot was formed by 24 quails with a total of 480 birds. Performance (production and egg weights, feed intake, feed conversion ratio per kg egg mass and per dozen eggs, viable eggs and egg viability) and egg quality (eggshell thickness and yield, specific weight and Haugh unit) were evaluated. Treatment differences were compared using the Scott-Knott test (5%). Wheat bran and high- zinc diets yielded poorer averages of egg production and feed conversion ratioper dozen eggs. Studied treatments had no influence on egg quality. Hence, we can conclude that corn- only or corn and soybean bran only feeds can be adopted as forced molting methods in Japanese quails instead of traditional fasting methods.